High Bifurcation of the Common Carotid Artery with Pentafurcation of the External Carotid Artery: Case Series with Review of Literature - Manokaran, Aarthi; Gaikwad, Manisha R; A, Baskar; Gopalakrishnan, Murugan; Ravi, Praveen Kumar (Acta medica Lituanica, 2025)
The bifurcation of the Common Carotid Artery (CCA) is a pivotal anatomical landmark in head and neck surgeries, particularly affecting procedures such as carotid endarterectomy. Typically occurring around the C3-C4 intervertebral disc, variations in its location can complicate surgical access and pose risks of nerve injury. In this case report, three rare bilateral high bifurcations of the CCA at the C2 and C2/3 vertebrae levels are documented. Additionally, an unusual pentafurcation of the External Carotid Artery (ECA) and bilateral superior thyroid artery are observed, arising directly from the CCA. The high bifurcation presents challenges due to its proximity to nerves such as the hypoglossal nerve, potentially leading to complications such as dysphagia or speech impairment. Furthermore, it complicates procedures like carotid endarterectomy, necessitating additional techniques for adequate exposure and increasing risks of Internal Carotid Artery (ICA) thrombosis. Detailed preoperative imaging before surgery is important for effective planning and minimizing the surgical risk. Anatomical variation, such as the vascular structure, can significantly affect surgical and interventional outcomes. Identifying these differences through meticulous evaluation enables surgeons to anticipate potential challenges, reduce complications, and enhance patient outcomes.
Keywords: high carotid bifurcation; carotid surgery; preoperative imaging